The 272 : the families who were enslaved and sold to build the American Catholic Church - Swarns, Rachel L. (Random House, 2023)
"In 1838, a group of America's most prominent Catholic priests sold 272 enslaved people to save their mission, the fledgling Georgetown University. Journalist, author, and professor Rachel L. Swarns has broken new ground with her prodigious research into a history that the Catholic Church has edited out of its own narrative. Beginning in the present, when two descendants of a family enslaved by the church reconnect, Swarns follows their ancestors through the centuries to understand how slavery enabled the Catholic Church to establish a foothold in America and fuel its expansion. Ann Joice, a free Black woman and progenitor of the Mahoney family, sailed to Maryland in the 1600s as an indentured servant, but her contract was burned and her freedom stolen. Harry Mahoney, Ann's grandson, saved lives and a Church fortune with his quick thinking during the British incursions in the War of 1812. But when the Jesuits fell into debt and were at risk of losing Georgetown University, they sold 272 people, including Harry's daughter Anna, to plantation owners in the Gulf. Like so many of the families the Jesuits' sale tore apart, Anna would never again see her father or her beloved sister Louisa who stayed with Harry in Maryland. Her descendants would work for the Jesuits well into the 20th century. The two sides of the family would remain apart until Swarns' original reporting on the 1838 sale in the New York Times reunited them and led directly to reparations for all the descendants of the enslaved"--